Некоторые сведения о губоногих многоножках Ростовской области - Миноранский, В.А. (Вестник зоологии, 1977)
In the territory of the Rostov Region 18 species of Chilopoda are found 9 of which are geophilous, 6 belong to Lithobiomorpha, 2 to Scolopendromorpha and 1 to Scutigeromorpha. Species composition and the member of Myriopoda in different natural and cultural cenoses vary considerably. Dependence of the Myriopoda population density on the type of plots (moisture degree, tillage) as well as the degree of the Myriopoda concentration at different depth are shown.